APPLICATION OF THE EKOLISTIC WAY CURRICULUM IN ISLAMIC RELIGIOUS EDUCATION LEARNING TO SHAPE STUDENTS' CHARACTER AT MA'HAD TEE BEE SURABAYA - Nurul istiqomah; Eli Masnawati; Solchan Gozali (Hijri, 2026)
This study aims to describe and analyze the application of The Ekolistic Way Curriculum in Islamic Religious Education (IRE) learning and its impact on shaping students' character at Ma'had Tee Bee Surabaya. The research approach used is descriptive qualitative with data collection methods through in-depth interviews, participatory observation, and documentation studies. The results show that this curriculum is implemented holistically through the integration of three main pillars: (1) making God the center (spiritual), (2) humanizing humans (social), and (3) naturalizing nature (ecological). The learning process is not only cognitive but also emphasizes exemplary behavior, habituation, and the creation of a contextual educational environment. The character formed in students reflects values such as discipline, empathy, social responsibility, and environmental care. The success of the curriculum implementation is supported by community commitment, the exemplary role of central figures, and a sustainable mentoring system. This study concludes that The Ekolistic Way Curriculum can be a transformative character education model relevant to modern educational challenges